Upper Extremity Diaphyseal Osseous Gap Reconstruction with Free Vascularized Bone Flaps: A Scoping Review - Naga, Hani I.; Kim, Joshua; Dunworth, Kristina; Oleck, Nicholas; Emovon, Emmanuel; Graton, Margaret; Mithani, Suhail K. (Journal of Reconstructive Microsurgery, 2024)
Background Reconstruction of upper extremity osseous diaphyseal defects often requires complex reconstructions. In this study, we characterized and summarized the available literature on free vascularized bone flap (VBF) reconstruction for upper extremity diaphyseal defects.Methods A scoping review using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for Scoping Reviews was conducted. A literature search of major electronic databases was conducted to identify journal articles relating to the management of VBF reconstruction of upper limb long bone defects. Articles with patient-level data were included. Descriptive statistics were performed using Python.Results Overall, 364 patients were included in this study. The most common indications for VBFs included atrophic nonunion (125, 34.3%), postoncologic resection (125, 34.3%), septic nonunion (56, 15.4%), and trauma (36, 9.9%). Mean defect size was 8.53 ± 5.14 cm. A total of 67 (18.4%) cases had defects < 6 cm, and 166 cases (45.6%) had defects > 6 cm. The fibula was the most utilized VBF (272, 74.73%), followed by the medial femoral condyle flap (69, 18.96%). Overall, primary union rate was 87.1%. Subsequent flap fracture rate was 3.3%. There were only two (0.6%) VBF losses reported in the included cases, and donor-site complications were similarly rare (17, 4.7%).Conclusion VBF reconstruction is often utilized for postoncologic defects and recalcitrant nonunions. The fibula is the most utilized VBF, but the medial femoral condyle flap is used frequently for smaller defects. VBF reconstruction demonstrates high union rates and low flap fracture rate across indications.
Keywords: upper extremity; osseous defects; fibula; vascularized bone; microsurgery